The Influence of Leadership and Compensation on Work Objectives of Employees of PT. Rava Ataya (Konawe Regency, South Sulawesi, Southeast Sulawesi) - Mariani, Mariani; Imran, Imran; Rajuddin, Wa Ode Nursaadha; Andriani, Dian Susi Andriani (International Journal of Management and Education in Human Development, 2022)
This study aimed to examine and explain the effect of leadership and compensation on the job satisfaction of employees of PT. Rava Ataya (South Konawe Regency, Southeast Sulawesi) either partially or simultaneously. This quantitative research approach uses a survey method with an explanatory research design. They are collecting data using an instrument in the form of a questionnaire—sampling technique with the non-probability sampling method. The type of non-probability sampling used is the census sample in this study, with 54 respondents. The analytical tool used is multiple linear regression. Researchers used SPSS version 24.00 for windows to manage data and draw conclusions. The results showed a positive and significant influence between leadership and compensation on employee job satisfaction, either partially or simultaneously. With a high R-Square value, this variable can affect job satisfaction research variables. Subsequent research examines other variables, such as motivation, compensation, work environment, and the dependent variable of employee performance.